Vocal performance during spontaneous song is equal in male and female European robins. (November 2022) - Dudouit, Charlène; Maury, Chloris; Bosca, Julie; Bakker, Antje; Gahr, Manfred; Aubin, Thierry; Rybak, Fanny; Geberzahn, Nicole
Abstract : The song of male birds is implicated in mate attraction and territory defence and assumed to evolve through sexual selection. Song production is hypothesized to represent a biomechanical challenge under physical, respiratory and neural limitation, leading to trade-offs. Although both sexes sing in numerous species, vocal performance has been little studied in females. European robins, Erithacus rubecula, of both sexes sing in autumn and winter to defend exclusive individual territories. We recorded robins singing spontaneously, that is, when not engaged in overt territorial interactions. We identified a trade-off between two acoustic parameters: (1) the frequency ratio between successive song elements and (2) the duration of gaps between these elements. This trade-off might represent a vocal production limit. To compare vocal performance between the sexes we used two measures: vocal gap deviation (the difference between how the bird sings and the theoretical performance maximum according to the putative vocal production limit we had identified) and sound density (the proportion of the song over which sound is present). Males and females did not differ in these two measures of vocal performance suggesting that the territory defence function of the song is used in social competition with members of either sex. In both sexes, vocal performance was not correlated with morphometric measures and repeatability coefficients were very small. Thus, vocal performance probably does not convey information about the signaller's body size or body condition, at least in spontaneous song of robins. These results inform the debate on selection forces driving female song. Highlights: Birdsong is subject to vocal production limits. Certain birds sing close to such limits and thus reach high vocal performance. Female birdsong and female vocal performance have been understudied. Female European robins reach the same level of vocal performance as males in winter. Female song seems important in territorial defence against male and female robins.